Implementation of The Application of Election Crime Sanctions in South Sulawesi Province - AR, Andi Baso Zulfakar; Zulfikar, Muh. Reza (Manunggal Halim Jaya, 2025)
The application of sanctions for election crimes in South Sulawesi Province is guided by Government Regulation instead of Law Number 1 of 2022 and Article 1, Number 1, concerning election offenses related to election administration violations. This study adopts a descriptive qualitative research approach. It aims to gather field information through questionnaires distributed to employees and Acting KPU (General Election Commission) officials, specifically focusing on cases of fraud and political money during the election process in Makassar City, South Sulawesi Province. Makassar City was chosen as the research location due to its strategic role as a political center in South Sulawesi and its favorable conditions for supporting the study.